Social Support from Family and Peers in Elderly as Effort in Improving the Psychological Well-being during Covid-19 Pandemicat Surabaya - Pipit Festi Wiliyanarti; Mundakir (Indian Journal of Forensic Medicine & Toxicology, 2021)
Social support is important in improving the health of the elderly. The spread of Covid-19 can reduce thephysical and mental condition of the elderly. The purpose of this study was to analyze the social support offamily and fellow elderly in the elderly as an effort to improve their psychological well-being during theCovid-19 period.This research was a survey research, based on its character, it is an analytical description with a crosssectional design. The population is all elderly in Surabaya and Madura areas.The sample was 305 partlyelderly from 3 cities of Surabaya, Pamekasan, and Sumenep chosen through random sampling technique. Theindependent variable wassocial support, which is the social support from family and friends, while thedependent variable wasthe level of psychological well-being of the elderly. The research instrument indetermining thesocial support from family, the social support from peer and the level of psychological wellbeingwas questionnaire. Meanwhile, the data analysis was conducted by using logistic regression.The results of peer support obtained p = 0.127; Family support obtained p = 0.000;Rsquare was 0.080,indicating that the family social support affected the psychological well-being of the elderly. It is expectedthatthe elderly can improve their health during the Covid-19 pandemic by carrying out positive activities bothat home and in the community. Family support and health services for the elderly are needed in improvingthe psychological well-being of the elderly. Psychological well-being must always be improved so that thehealth of the elderly can be achieved and the elderly can pass through the pandemic well. This requiresgovernment participation and policies to make it happen.